Unraveling the anatomy of toe extensors: An aid to the clinical implications - Noor us Saba; Pratibha Shakya; Heena Singh; Nikhil Aggarwal; Punita Manik; Navneet Kumar (Asian Journal of Medical Sciences, 2024)
Background: The extensor tendons of the foot are crucial for maintaining the intricate movements and stability of the foot and ankle complex. Understanding these variations is essential for health-care professionals involved in foot-related pathologies. Aims and Objective: The study was conducted to identify and document variations in extensor tendons of the foot during routine dissection of human cadavers and to highlight their clinical significance. Materials and Methods: This was an observational study conducted in the Department of Anatomy, King George’s Medical University, Lucknow, India. Eight embalmed cadavers were examined, and the dorsum of the foot was dissected to explore the proximal and distal attachments of extensor muscles. Results: We observed unilateral variations in extensor tendons of the feet of three limbs during routine dissection. First case showed a bifurcation of extensor hallucis longus, giving tendons to great toe as well as 2nd toe. Second case showed a variation in extensor digitorum longus tendon of the 4th toe giving lateral and medial slips along with its main tendon. The medial slip further gave medial and lateral divisions to merge distally with the long tendons of 3rd and 4th toe, respectively. The third case depicted the bifurcation of extensor hallucis brevis to give tendinous slips to great toe and 2nd toe, respectively. Conclusion: Knowledge of these variations in extensor tendons of foot is crucial for accurate interpretation of diagnostic imaging, surgical planning, and optimizing treatment outcomes.